Evaluation of Sensation on Mastectomy Skin Flaps following Immediate Breast Reconstruction - Akdeniz Dogan, Zeynep; Farhadi, Jian (Journal of Reconstructive Microsurgery, 2020)
Background During a subcutaneous mastectomy, nerves are severed and patients lose sensation on the breast skin. The aim of this study is to investigate factors that have impact on the sensation of the mastectomy flaps and patients' own perception regarding overall breast skin sensation.Patients and Methods Patients who have undergone skin sparing or nipple sparing mastectomy with immediate reconstruction with either an implant or autologous tissue were included. Sensory assessment was performed at least 12 months after surgery using Semmes–Weinstein monofilaments (Aesthesio, San Jose, CA). The breast envelope was divided into four quadrants, and one measurement from each quadrant was recorded. Patients were also asked to fill out a questionnaire before the examination.Results A total of 59 breasts in 40 women were examined. In lower medial quadrant, significantly more patients reported “no sensation” in the radiated group than the nonradiated group. In upper medial quadrant and lower lateral quadrant, patients with NSM reported better sensation than patients with skin sparing mastectomy (SSM).Conclusion Vascularized tissue did not improve sensory recovery. There was no relationship between sensation and the preoperative cup size and the number of revision surgeries. Irradiation was associated with higher sensory thresholds in lower medial quadrant. Nipple sparing mastectomy was associated with lower sensory thresholds in two quadrants compared to SSM. Independent of all variables none of the patients reported normal sensation.
Keywords: breast reconstruction; mastectomy skin flap; sensation; Semmes–Weinstein